PERAN PENGALAMAN KERJA, KOMITMEN DAN MOTIVASI TERHADAP PROFESIONALISME PEGAWAI DI KECAMATAN LENTENG KABUPATEN SUMENEP - Siti Nur Fadlilah; Chamariyah; Indra Prasetyo (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
The purpose of study are 1). To describe work experience, commitment, motivation, and professionalism of employees in Lenteng District, Sumenep Regency. 2) To view and analyze work experience, commitment, motivation simultaneously have a significant effect on employee professionalism in Lenteng District, Sumenep Regency 3). To view and analyze work experience, commitment, motivation partially significant effect on employee professionalism in Lenteng District, Sumenep Regency. 4). To find out which variables between work experience, commitment, motivation have dominant influence on employee professionalism in Lenteng District, Sumenep Regency. This type of research is explanatory research, the research approach uses a quantitative approach, data analysis uses SPSS. The research sample was 35 employees. The results showed that : 1). Simultaneously, work experience, commitment and motivation have a significant effect on Employee Professionalism in Lenteng District, Sumenep Regency, it is evidenced by the calculated F value of 1.706 with a significance level known from the sig value of 0.001 (less than 0.05). 2). Partially, work experience, commitment and motivation have a significant effect on Employee Professionalism in Lenteng District, Sumenep Regency. 3). Based on the test results, it is known that motivation affects the professionalism of employees in Lenteng District, Sumenep Regency; evidenced by the t value is 1.741 with a significance level of 0.001 (less than 0.05).